Polyphony and Ideological Presence an Approach in The Novel “Al_ Tanki” By Alia Mamdouh - Nizar Frak Ali Al-Hassany (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This critical paper seeks to provide a reading of the novel “Al Tanki” through the concepts of multiple voices and the ideological presence of the characters within the novel, and then the ideology adopted by the narrative work. This study also works to clarify the concept of narrative fragmentation, breaking the development of traditional narrative, building a new architecture for the worlds of narrative narrative, exploring the fabric of Alia Mamdouh’s novel “Al_ Tanki”, and attempting to reveal the artistic impact of these two concepts on the form and content of the novel.